2016
DOI: 10.1080/03630269.2016.1183212
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Relationship Between Hb F Levels and Nucleated Red Blood Cells with Morbidity in Non Transfusion-Dependent Thalassemia Patients

Abstract: Recognition of risk factors of morbidities in patients with β-thalassemia intermedia (β-TI) is an important issue that must be evaluated. Non transfusion-dependent thalassemia patients referred to the outpatient clinic of Shiraz University of Medical Science, Shiraz, South Iran were enrolled in this study between 2013 and 2014. Two peripheral blood smears were prepared for evaluating developmental stage of normoblasts. One hundred and thirty-one patients with ages ranging from 3 to 42 years (mean: 23.35 ± 7.9)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…Consistent with the findings from other studies, the observed reduced WBCs, and platelets in the HU+ participants in our study participants confirms the cytoreductive effect of HU. 18 , 19 The findings of higher percentage HbF levels in the HU-treated participants are also consistent with what is generally known about the genetic modifiers of HbF in SCD.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Consistent with the findings from other studies, the observed reduced WBCs, and platelets in the HU+ participants in our study participants confirms the cytoreductive effect of HU. 18 , 19 The findings of higher percentage HbF levels in the HU-treated participants are also consistent with what is generally known about the genetic modifiers of HbF in SCD.…”
Section: Discussionsupporting
confidence: 81%
“…Interestingly, we observed a slightly reduced Hb level in the HU+ group and speculate that, this could be due to crenation and subsequent lysing of RBC’s since HU plays a role in RBC differentiation. 19 …”
Section: Discussionmentioning
confidence: 99%